2007
DOI: 10.1002/ppul.20715
|View full text |Cite
|
Sign up to set email alerts
|

Lipid laden macrophage indices and reflux finding score in canine gastroesophageal reflux model

Abstract: Acid reflux to the proximal esophagus of this animal model did not cause laryngeal exposure to acid or aspiration of gastric content. The results of this study suggest that presence of GER, secondary to lower esophageal dysfunction is not necessarily associated with upper and lower airway pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…6 Also, dogs have a high proportion of lipid-laden macrophages, compared with other species, and experimental induction of gastroesophageal reflux did not increase this index value. 28,29 Detection of pepsin in bronchoalveolar lavage fluid can be used to diagnose aspiration injury in children with gastroesophageal reflux. 30 Unfortunately, collection of airway samples was rarely performed in the dogs of the present study, thereby precluding assessment of lipid-laden macrophages or pepsin concentration.…”
Section: Discussionmentioning
confidence: 99%
“…6 Also, dogs have a high proportion of lipid-laden macrophages, compared with other species, and experimental induction of gastroesophageal reflux did not increase this index value. 28,29 Detection of pepsin in bronchoalveolar lavage fluid can be used to diagnose aspiration injury in children with gastroesophageal reflux. 30 Unfortunately, collection of airway samples was rarely performed in the dogs of the present study, thereby precluding assessment of lipid-laden macrophages or pepsin concentration.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered that partial myectomy could result in efficacious gastroesophageal reflux in rabbits [14]. Although Nino [8] used this method in dogs, other authors found that the partial myectomy was sub-optimal as a gastroesophageal reflux model compared with the total myectomy in rats [15]. For this study, we chose a total myectomy rabbit model to induce more gastric contents into the esophagus even pharynx and larynx.…”
Section: Discussionmentioning
confidence: 99%
“…However, in LPR, it is not clear whether dysfunction of the LES harms the upper airway. Nino [8] created a canine reflux model and found that there was no significant difference in the RFS, lipidladen macrophage index (LLMI) or bronchoalveolar lavage fluid differential before and 2 weeks after partial myectomy. However, the short study duration and lack of histopathology of the larynx weaken the credibility of this study [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Maronian et al [12] patients with symptoms such as hoarseness, aphonia, cough, and throatclearing with abnormal pH studies were enrolled as reflux laryngitis, and they were not able to come up with any characteristic histological features of reflux-induced laryngitis in patients with proven GERD. Nino et al [13] defined the reflux index, duration of longest reflux episode, and number of reflux episodes confirmed with pH probe as the evaluation of gastroesophageal reflux (GER), and they defined laryngoscopic findings as index of reflux. However they did not find any correlation between presence of GER and laryngoscopic findings.…”
Section: Discussionmentioning
confidence: 99%